In vitro Selection of Probiotics for Microbiota Modulation in Normal-Weight and Severely Obese Individuals: Focus on Gas Production and Interaction With Intestinal Epithelial Cells - Nogacka, Alicja Maria; de los Reyes-Gavilán, Clara G.; Arboleya, Silvia; Ruas-Madiedo, Patricia; Martínez-Faedo, Ceferino; Suarez, Adolfo; He, Fang; Harata, Gaku; Endo, Akihito; Salazar, Nuria; Gueimonde, Miguel (Frontiers in Microbiology, 2021)
The intestinal microbiota plays important roles in the maintenance of health. Strategies aiming at its modulation, such as probiotics, have received a deal of attention. Several strains have been studied in different in vitro models; however, the correlation of results obtained with the in vivo data has been limited. This questions the usefulness of such in vitro selection models, traditionally relying on over-simplified tests, not considering the influence of the accompanying microbiota or focusing on microbiota composition without considering functional traits. Here we assess the potential of six Bifidobacterium, Lactobacillus and Lacticaseibacillus strains in an in vitro model to determine their impact on the microbiota not just in terms of composition but also of functionality. Moreover, we compared the responses obtained in two different population groups: normal-weight and severely obese subjects. Faecal cultures were conducted to evaluate the impact of the strains on specific intestinal microbial groups, on the production of short chain fatty acids, and on two functional responses: the production of gas and the interaction with human intestinal epithelial cells. The response to the different probiotics differed between both human groups. The addition of the probiotic strains did not induce major changes on the microbiota composition, with significant increases detected almost exclusively for the species added. Higher levels of gas production were observed in cultures from normal-weight subjects than in the obese population, with some strains being able to significantly reduce gas production in the latter group. Moreover, in obese subjects all the Bifidobacterium strains tested and Lacticaseibacillus rhamnosus GG were able to modify the response of the intestinal cells restoring values similar to those obtained with the microbiotas of normal-weight subjects. Our results underline the need for the screening and selection of probiotics in a target-population specific manner by using appropriate in vitro models before enrolling in clinical intervention trials.